A case of renovascular hypertension with incidental primary bilateral macronodular adrenocortical hyperplasia. (6th August 2020) - Higashitani, Takuya; Karashima, Shigehiro; Aono, Daisuke; Konishi, Seigoh; Kometani, Mitsuhiro; Oka, Rie; Demura, Masashi; Furukawa, Kenji; Yamazaki, Yuto; Sasano, Hironobu; Yoneda, Takashi; Takeda, Yoshiyu
Abstract : Summary: Renovascular hypertension (RVHT) is an important and potentially treatable form of resistant hypertension. Hypercortisolemia could also cause hypertension and diabetes mellitus. We experienced a case wherein adrenalectomy markedly improved blood pressure and plasma glucose levels in a patient with RVHT and low-level autonomous cortisol secretion. A 62-year-old Japanese man had been treated for hypertension and diabetes mellitus for 10 years. He was hospitalized because of a disturbance in consciousness. His blood pressure (BP) was 236/118 mmHg, pulse rate was 132 beats/min, and plasma glucose level was 712 mg/dL. Abdominal CT scanning revealed the presence of bilateral adrenal masses and left atrophic kidney. Abdominal magnetic resonance angiography demonstrated marked stenosis of the left main renal artery. The patient was subsequently diagnosed with atherosclerotic RVHT with left renal artery stenosis. His left adrenal lobular mass was over 40 mm and it was clinically suspected the potential for cortisol overproduction. Therefore, laparoscopic left nephrectomy and adrenalectomy were simultaneously performed, resulting in improved BP and glucose levels. Pathological studies revealed the presence of multiple cortisol-producing adrenal nodules and aldosterone-producing cell clusters in the adjacent left adrenal cortex. In the present case, the activated renin-angiotensin-aldosterone system and cortisol overproduction resulted in severe hypertension, which was managed with simultaneous unilateral nephrectomy and adrenalectomy. Learning points: Concomitant activation of the renin-angiotensin-aldosterone system and cortisol overproduction may contribute to the development of severe hypertension and lead to lethal cardiovascular complications. Treatment with simultaneous unilateral nephrectomy and adrenalectomy markedly improves BP and blood glucose levels. CYP11B2 immunohistochemistry staining revealed the existence of aldosterone-producing cell clusters (APCCs) in the adjacent non-nodular adrenal gland, suggesting that APCCs may contribute to aldosterone overproduction in patients with RVHT.